A new look at the role of nitric oxide in preeclampsia: Protein S-nitrosylation - Nunes, Priscila Rezeck [UNESP] (2022)
The formation of S-nitrosothiols (SNOs) occurs with the reaction of nitric oxide (NO) and free thiol groups in proteins. This process, called S-nitrosylation, allows NO to interfere with or even modulate a variety of cellular functions, culminating with the modification of protein trafficking, redox state, and cell cycle. Furthermore, NO plays a role in modulating a wide range of functions in endothelial cells specifically, including inflammation, apoptosis, permeability, migration, and cell growth. As such, NO acts as a mediator in several physiological processes. The interaction between endothelial nitric oxide synthase (eNOS) and proteins that are to be targeted for S-nitrosylation is a key determinant of the specificity of NO signaling. Deficits in the bioavailability of NO have been associated with pregnancy-related disorders, such as preeclampsia (PE). The study of S-nitrosylation in PE, as well as the identification of targeted proteins, may contribute to a better understanding of its pathophysiology and the development of drugs for the treatment of PE patients. In this review, we aimed to present the mechanism of S-nitrosylation, the regulatory pathways, and some proteins by which S-nitrosylation can modulate NO availability with a potential impact on PE.